2019
DOI: 10.1371/journal.pone.0223104
|View full text |Cite
|
Sign up to set email alerts
|

Social resistance drives persistent transmission of Ebola virus disease in Eastern Democratic Republic of Congo: A mixed-methods study

Abstract: BackgroundThe second largest Ebola virus disease (EVD) epidemic in history is currently raging in Eastern Democratic Republic of Congo (DRC). Stubbornly persistent EVD transmission has been associated with social resistance, ranging from passive non-compliance to overt acts of aggression toward EVD reponse teams.MethodsWe explored community resistance using focus group discussions and assessed the prevalence of resistant views using standardized questionnaires.ResultsDespite being generally cooperative and app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 32 publications
1
60
0
Order By: Relevance
“…20 The chronic threats to security have long been neglected by the national government and the international community. 17 We selected 3 IDP camps (Mwangaza, Masosi, and Luvangira) located 2 to 5 km from the rural commune of Oïcha, North Kivu. These temporary settlements consisted of groups of IDPs sheltered in school buildings or mud/thatch dwellings on public grounds.…”
Section: Study Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…20 The chronic threats to security have long been neglected by the national government and the international community. 17 We selected 3 IDP camps (Mwangaza, Masosi, and Luvangira) located 2 to 5 km from the rural commune of Oïcha, North Kivu. These temporary settlements consisted of groups of IDPs sheltered in school buildings or mud/thatch dwellings on public grounds.…”
Section: Study Settingmentioning
confidence: 99%
“…28 The choice of questionnaire items was guided by a need for contextually appropriate questions for low-income settings. We also drew on past experience from past surveys conducted in IDP camps in the area [29][30][31][32] and from the recent Ebola virus disease epidemic 16,17,33 to design questions that would be relevant and understood by the participants. A local Congolese physician (KMC) with tacit knowledge of the circumstances, culture, and language of the IDPs chose the appropriate wording of the questions and adapted the content of the questionnaire to the conditions in the IDP camp.…”
Section: Survey Questionnairementioning
confidence: 99%
“…47 A study conducted among focus groups in the DRC found that 72% of respondents were dissatisfied with and mistrustful of the public health and government response, while 15% expressed that they would not comply with public health recommendations regarding isolation, quarantine at treatment centers, and safe burial in the case of illness or death in a family member. 48 In 2019, in the DRC, Doctors Without Borders/Médecins Sans Frontières recorded 300 attacks against healthcare workers, including an arson attack against and Ebola treatment center in Katwa. 49 Similar misinformation circulated during the 2014-2016 Ebola outbreak in West Africa-largely in Guinea, Liberia, and Sierra Leone-both in these countries and internationally.…”
Section: Effect Of Social Media Misinformation and Disinformationmentioning
confidence: 99%
“…Hospitalization and death happen away from the public eye, and our changing understanding of the mechanism of transmission, the risk of mortality and the long-term consequences of the disease have favored the spread of misinformation. The spread of confusion and misinformation has been a common feature for other novel pathogen-induced pandemics such as Ebola (1,11,12) and the 1918 Flu (13). While the existence of pandemic denialism was easy to anticipate (14), the unique characteristics of SARS-CoV-2 amplify its effect.…”
Section: Introductionmentioning
confidence: 99%